Integration of green skills in sustainable development in technical and vocational education - Kamis, Arasinah; Alwi, Amarumi; Hj Ismail, Bushra Limuna; Normah, Zakaria; Nur Yunus, Faizal Amin (University Grants Commisions, 2017)
TVET or Technical and Vocational Education, Pendidikan Teknikal dan Vokasional in Malaysia (PTV) plays an important role in contributing to the source of skilled manpower. PTV transformation needs to emphasise sustainable development in producing competent students. Green skills that have a significant association with green technology will contribute to sustainable development in terms of the environment, economy and social activities. Indeed, green skills need to be incorporated in PTV as one of the measures to provide skilled labour and at the same time act as an agent of sustainable development in various aspects. This article explores the integration of green skills in the sustainable development of PTV in Education Sustainability Development (ESD) as a method of preserving and conserving the environment.